General Chemistry Without Orbitals - Lamoureux Lamontagne, Guy (2020)
We illustrate the solutions of Schroedinger's equation for the hydrogen atom in coordinates of all four systems, and differentiate the applicability of orbitals in these four systems. We present reasons that future textbooks of general chemistry should exclude orbitals and discuss the teaching of general chemistry on this basis. The incompatibility of molecular structure and quantum mechanics is discussed before a conclusion that quantum mechanics and its orbital artifacts are irrelevant for general chemistry